2018
DOI: 10.1186/s12894-017-0312-5
|View full text |Cite
|
Sign up to set email alerts
|

Suprapubic tube versus urethral catheter drainage after robot-assisted radical prostatectomy: a systematic review and meta-analysis

Abstract: BackgroundProstate cancer is one of the most common cancers in the elderly population. The standard treatment is radical prostatectomy (RARP). However, urologists do not have consents on the postoperative urine drainage management (suprapubic tube (ST)/ urethral catheter (UC)). Thus, we try to compare ST drainage to UC drainage after robot-assisted radical prostatectomy regarding to comfort, recovery rate and continence using the method of meta-analysis.MethodsA systematic search was performed in Dec. 2017 on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 17 publications
3
28
0
1
Order By: Relevance
“…A systematic review by Zumstein et al of 61 member states of the Societé Internationale d’Urologie (SIU) found no guidelines for urolithiasis amongst Sub-Saharan states. 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review by Zumstein et al of 61 member states of the Societé Internationale d’Urologie (SIU) found no guidelines for urolithiasis amongst Sub-Saharan states. 8 …”
Section: Discussionmentioning
confidence: 99%
“…The surgical management of kidney and ureteral stones is based on the stone location, size, the patient’s preference and the institutional capacity. 8 Over past decades, there has been a paradigm shift from open surgery to endourology in the management of upper tract urolithiasis. To date, the available modalities in the management of urolithiasis include external shock wave lithotripsy (ESWL), percutaneous nephrolithotomy (PCNL), ureterorenoscopy (URS) including flexible and semirigid ureteroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The combined effect of miR-17-5p/3p led to a proliferative and migratory phenotype [ 73 ]. Additional examples include oncogenic pre-miR-10b in esophageal squamous cell carcinoma (ESCC) [ 74 , 75 ], pre-miR-21 in ovarian cancer [ 98 , 99 , 100 ], and pre-miR-221 in PCa [ 76 , 77 ], the dual tumor-promoting strands in all these cases have been identified by individual studies. First, starvation-induced miR-10b-5p expression increased the autophagic flux in ESCC during nutrient deprivation, and DAZ associated protein 1 ( DAZAP1 ) was the direct target and mediator of this phenomenon.…”
Section: Functional Annotation Of Premature Mirnas In Cancersmentioning
confidence: 99%
“…MiR-221-5p expression was elevated in tumor and adjacent tissues of clinical samples, indicating its oncogenic role in prostate carcinogenesis. Ectopic miR-221-5p manipulation proved that miR-221-5p enhanced the migratory and proliferative capabilities of PCa cells in vitro, and suppressers of cytokine signaling 1 ( SOCS1 ), an established tumor suppressor, was validated to be the direct target of 3’-UTR luciferase reporter assay [ 76 ]. MiR-221-3p is reported to participate in the development or maintenance of castration resistant prostate cancer (CRPC) phenotype, but the underlying mechanism remains unknown [ 105 ].…”
Section: Functional Annotation Of Premature Mirnas In Cancersmentioning
confidence: 99%
“…Suprapubic tube placement, therefore, is not routinely recommended for urine drainage after a RP. 61…”
Section: Barbed Suturesmentioning
confidence: 99%